2010
DOI: 10.1037/a0017954
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of Structural Ecosystems Therapy for HIV medication adherence with African American women.

Abstract: A systemic family therapy intervention, Structural Ecosystems Therapy (SET), has been shown to promote adaptation to living with HIV by reducing psychological distress and family hassles. This investigation examines the effect of SET on HIV medication adherence relative to a person-centered condition and a community control condition. Medication adherence was assessed on 156 trial participants. Results of a two-part model showed that SET was significantly more likely to move women to high levels of adherence (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…Of the 29 studies in the meta-analysis, only one study formally tested change in depressive symptoms or psychological distress as a predictor of change in ART adherence; the study found no significant relationship between the rate of change in psychological distress and change in adherence (40). Studies of collaborative care for depression (23) and cognitive behavioral stress management (22, 41) did show improvements in depression outcomes but not ART adherence.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 29 studies in the meta-analysis, only one study formally tested change in depressive symptoms or psychological distress as a predictor of change in ART adherence; the study found no significant relationship between the rate of change in psychological distress and change in adherence (40). Studies of collaborative care for depression (23) and cognitive behavioral stress management (22, 41) did show improvements in depression outcomes but not ART adherence.…”
Section: Resultsmentioning
confidence: 99%
“…Familial conflict refers to disagreements between family members, often immediate family who are same household residents, which can be either acute or chronic [29,30,31]. Literature on familial conflict suggests that HIV diagnosis represents a chronic stressor, which may reinforce substance use and/or mental illness among PLHIV [27,28,30,32].…”
Section: Introductionmentioning
confidence: 99%
“…Structural Ecosystems Therapy (SET; Mitrani et al, 2009) is a family based intervention for poor inner-city HIV+ women targeting psychosocial factors (e.g., reduced family stress and increased family support) associated with progressions in HIV symptoms. In a previous randomized clinical trial, SET showed efficacy in reducing psychological distress and family-related irritation (Szapocznik et al, 2004), lowering rates of relapse (Feaster, Burns, et al, 2010), and increasing medication adherence (Feaster, Brincks, et al, 2010). The current study extends previous findings by testing the efficacy of SET for improving HIV medication adherence and reducing relapse as compared to a Health Group (HG) intervention for women in recovery.…”
Section: Introductionmentioning
confidence: 99%